Spectrum Renting with Two Finite Source Pools in Mobile Cellular Networks - Horvath, Adam; Berczes, Tamas (Communications - Scientific letters of the University of Zilina, 2015)
Spectrum renting is a technique for improving the efficiency of spectrum usage and alleviating the scarcity of the available spectrum in mobile cellular networks. Since the first proposal of spectrum pooling, several works have been done in this area. In this paper, we propose a finite-source queuing model in which service providers may rent each other’s unutilized frequency bands. Our model contains two source pools: one for subscribers generating fresh calls in the investigated mobile cell, and another for modeling handover calls. The model considers the traveling of subscribers over the borders of the investigated mobile cell, too. Moreover, we take into account the retrial phenomenon caused by the impatience of subscribers. It has been already shown in the literature that the use of spectrum renting improves the main performance indices while the average profit rate increases. In this paper, we show how these parameters change with respect to the protection of handover calls.